Open-Economy Inflation Forecast Targeting - Kai Leitemo (Norges Bank, 2000)
The paper shows that the procedure of inflation forecast targeting arguably implemented by Sveriges Riksbank and the Bank of England may lead to high nominal and real variability; the latter being manifested most notably in the traded sector. A long inflation forecast targeting horizon results in extensive smoothing of interest rate movements. This implies only weak nominal interest rate responses to disequilibrium conditions, causing the real interest rate and hence the real exchange rate to fluctuate persistently. The paper offers an explanation for the recent large variability of Swedish inflation and UK manufacturing sector output.
hdl:11250/2500412
Keywords: E52; E47; E43; 330; inflation targeting; forecast targeting; monetary policy; small open economy